PENINGKATAN DAYA SAING PRODUK JAMU INSTAN MELALUI INOVASI KEMASAN SACHET DAN BRANDING DI KWT DESA PANYINGKIRAN KAB CIAMIS - Prabowo, Faizal Haris Eko; Satriadi, Dodi; Sihabudin, Aan Anwar; Ramadhan, Sarah Nuraeni; Rahmawati, Siti Amalia (Jurnal Abdi Insani, 2025)
The limited competitiveness of instant herbal drink products produced by the Women Farmers Group (KWT) Makmur in Panyingkiran Village, Ciamis, has become a crucial issue to address. The products were still constrained in terms of processing, packaging, and marketing, despite the abundance of local raw materials that could be developed further. This condition required an intervention to improve production capacity and business management so that the herbal drink products could compete in a wider market. This activity aimed to enhance the partners’ skills in production, management, marketing, and basic financial recording. The method consisted of problem identification, solution design, training on the use of three automatic machines, business management assistance, technology implementation, and evaluation. The program was carried out from April to December 2025 in Panyingkiran Hamlet, Panyingkiran Village, Ciamis District, West Java. Partners gained new skills in operating the machines, making production more efficient and hygienic. Production capacity increased from 0.5–1 kg to 3–5 kg per day. Production time decreased from 8–10 hours to 3–5 hours. Sales value rose from an average of IDR 80,000 to IDR 100,000–150,000 per period. Partners also improved their understanding of basic management, simple accounting, marketing, and product branding. The main obstacle was aligning schedules between the implementing team and the partners, while village officials and the community provided strong support. The program successfully improved the competitiveness of KWT Makmur through innovations in production, packaging, and marketing.